2016
DOI: 10.1063/1.4953570
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale studies of ionic closed membranes with polyhedral geometries

Abstract: High performance long wavelength infrared mega-pixel focal plane array based on type-II superlattices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, the canonical icosahedral shape of carboxysomes has been shown to sometimes become irregular or elongated in bacteria ( Iancu et al, 2010 ). Moreover, it has been suggested that pH variations and interactions with metallic cations may modify the shape of such compartments from spherical to faceted shapes ( Olvera de la Cruz, 2016 ). Finally, some proteins have been shown to stabilize ACC ( Rao et al, 2013 ) but this has never been tested on proteins composing the shell of bacterial microcompartments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the canonical icosahedral shape of carboxysomes has been shown to sometimes become irregular or elongated in bacteria ( Iancu et al, 2010 ). Moreover, it has been suggested that pH variations and interactions with metallic cations may modify the shape of such compartments from spherical to faceted shapes ( Olvera de la Cruz, 2016 ). Finally, some proteins have been shown to stabilize ACC ( Rao et al, 2013 ) but this has never been tested on proteins composing the shell of bacterial microcompartments.…”
Section: Discussionmentioning
confidence: 99%
“…This would be entropically unfavorable if Tween 40 molecules gathered at the side of Type A vesicles and were reorientated into new rims on Type B vesicles (i.e., the transition of Type A to Type B vesicles), although the energetical study should be examined. However, it has been shown that faceted structures can be low energy configurations of elastic spherical vesicles [23,[36][37][38]. If so, the faceted vesicles closer to the spherical vesicle (Type B) might be more stable than Type A vesicles.…”
Section: Discussionmentioning
confidence: 99%